Parental Gender Bias in Youth Employment Standards: Evidence from Upper Egypt - Saeed, Mahmoud (AUC Knowledge Fountain, 2026)
Youth unemployment remains a critical challenge in Egypt, with female labor force participation among the lowest globally. While structural factors such as limited job creation and public sector contraction are well-documented, the role of family-level decision-making in constraining women's labor market entry has received limited quantitative attention. This thesis examines parental gender bias in employment standards in Upper Egypt, investigating whether and how parents impose systematically different job requirements for daughters compared to sons. Using primary survey data from 17,284 unemployed youth aged 18-35 across six governorates, paired with responses from their parents, this study analyzes parental preferences across six dimensions: minimum wages, social insurance, health insurance, job type, working hours, and geographic mobility. The findings reveal substantial and statistically significant gender disparities across all dimensions. Parents set minimum wage requirements approximately 800 EGP lower for daughters than for sons, while simultaneously being 16 percentage points more likely to reject daughters' own stated wage preferences as insufficient. Parents also accept jobs without social insurance 2-5 percentage points more readily for daughters and show even larger gaps of 4-7 percentage points for health insurance. Geographic mobility emerges as the most severe constraint, with parents restricting daughters to village and district-level employment at rates 23-24 percentage points higher than for sons, effectively excluding young women from formal sector opportunities concentrated in distant urban centers. Both fathers and mothers exhibit similar restriction patterns. These restrictions combine discriminatory preferences, rational responses to hostile employment environments, and structural reproduction. When situated within Egypt's labor market transformation, characterized by public sector contraction and informal sector expansion, parental standards create impossible choices between excluding daughters entirely or accepting precarious employment. The study demonstrates that employment standards operate as systematic filters narrowing acceptable opportunities before youth engage with the labor market. The findings point to several potential policy avenues including job quality improvements, transportation infrastructure, harassment protections, and family engagement, while recognizing that translating these patterns into effective interventions requires addressing the complex interactions between family preferences, labor market structures, and institutional constraints.